Pemanfaatan Sampah Plastik dan Pengenalan Aplikasi Digital Plasticpay untuk Meningkatkan Pemberdayaan warga di wilayah Meruya - Jakarta Barat - Puspitarini, Sari; Ferranti , Putri Andari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2025)
Plasticpay is a digital-based social behavior change platform that invites people to exchange plastic bottle waste for points. This application is a digital platform based on digital social that creates applications and collection facilities and invites the community, public and private sectors to participate and collaborate in recycling activities to meet sustainable development goals. Through this plasticpay application service, people can participate in maintaining cleanliness, health and environmental sustainability so that the community participates in helping to facilitate business activities in Indonesia and can accelerate the circulation of money in the community which ultimately improves the community's economy. The community in the South Meruya area has so far utilized the use of the internet network. However, the community has not yet received sufficient understanding of the importance of protecting the environment independently, especially in managing plastic waste. Therefore, we are motivated to share knowledge through outreach programs to residents regarding the use of plastic waste and the introduction of the plasticpay digital application to increase the empowerment of residents in the Meruya - West Jakarta area as provisions in managing and utilizing plastic bottle waste, applying appropriate technology tools and machines to improve welfare, maintain cleanliness, health and environmental sustainability, and invite the community to participate and collaborate in recycling activities to meet sustainable development goals.